PERENCANAAN SALURAN IRIGASI SEKUNDER D.I KAUMAN KECAMATAN RAO SELATAN KABUPATEN PASAMAN - Harianto Harianto; Surya Eka Priana; Ana Susanti Yusman (Ensiklopedia Research and Community Service Review, 2022)
An Agrarian Country is an Indonesian country so it is reasonable if the main priority in the national agenda is centered on agriculture. In addition, the growth of population and industry is increasing. Therefore, it is necessary to improve the canals whose working function is decreasing. This Kauman Irrigation Area irrigates an area of 250 Ha of paddy fields. The source of water in the Kauman Irrigation District comes from the Batang river. Batang Lansat Kadap Irrigation Area is ± 45 km from Lubuk Sikaping city center. In Irrigation Network Planning, a design analysis must be done that includes rainfall analysis, discharge calculation, and channel dimensions. So that the irrigation system can be interpreted as an effort to provide maximum water supply. The main discharge of the planned channel is 3.24 m3/d, and the Max Debit is 2.44. The top dimension is 0.8, the bottom width is 0.6 and the height is 0.8. It can hold water when there is high rainfall. By improving the irrigation canals and providing enough water according to the needs, in planning, the dimensions of the canals are obtained through the process of rainfall by using the harpes method and the gumbel method. Keywords: food self-sufficiency, discharge, channel dimensions